Wearable devices and mobile technologies for supporting behavioral weight loss among people with serious mental illness. (30th October 2016) - Naslund, John A.; Aschbrenner, Kelly A.; Scherer, Emily A.; McHugo, Gregory J.; Marsch, Lisa A.; Bartels, Stephen J.
Abstract: Promoting physical activity is essential for addressing elevated cardiovascular risk and high obesity rates affecting people with serious mental illness. Numerous challenges interfere with exercise participation in this high-risk group including mental health symptoms, low motivation, and limited access to safe and affordable options for physical activity. Wearable devices and mobile health technologies may afford new opportunities for promoting physical activity and supporting behavioral weight loss efforts. This exploratory study examined whether daily step count measured using Fitbit wearable devices was associated with weight loss and improved fitness among individuals with serious mental illness enrolled in a 6-month lifestyle program. Participants ( n =34) had a schizophrenia spectrum disorder (23.5%), major depression (50.0%), or bipolar disorder (26.5%), and wore Fitbits most of the days (M=86.2%; SD=18.4%) they were enrolled in the study. At 6-months, higher average daily step count was associated with greater weight loss ( F =5.07; df =1, 32; p =0.0314), but not improved fitness ( F =1.92; df =1, 31; p =0.176). These findings demonstrate that encouraging participants with serious mental illness enrolled in lifestyle interventions to collect more steps may contribute to greater weight loss. This suggests that wearable devices may offer a feasible and potentially effective strategy for supporting behavioral weight loss in community mental health settings. Highlights: People with serious mental illness used wearable devices to support weight loss. Participants wore Fitbit devices for most of the days enrolled in the study. Higher average daily step count was associated with greater weight loss. Wearable devices could simplify efforts promoting physical activity in this group. Wearable devices appear effective for supporting behavioral weight loss programs.